Temporal analysis of distribution pattern of islet cells and antioxidant enzymes for diabetes onset in postnatal critical development window in rats - Gallego, Franciane Quintanilha [UNESP]; Miranda, Carolina Abreu [UNESP]; Sinzato, Yuri Karen [UNESP]; Iessi, Isabela Lovizutto [UNESP]; Dallaqua, Bruna; Pando, Rogelio Hernandez; Rocha, Noeme Sousa [UNESP]; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina [UNESP] (Elsevier, 2019)
Aim: At performing a temporal analysis of the distribution pattern of islet endocrine cells and antioxidant enzymes in diabetic rats during the post-natal critical development window. Main methods: The newborns received streptozotocin (STZ) at birth for diabetes induction, and control females received the vehicle. The animals were euthanized at different lifetimes: D5, D10, D15, and D30. Morphological analysis of pancreas and biochemical assays was performed. Key findings: The STZ-induced rats presented irregular shape of islet on D5 and there was an attempt to restore of this shape in other life moment studied. There was an increase progressive in islet area, however they maintained smaller than those of control rats, with lower labeling intensity for insulin, higher for glucagon and somatostatin, lower for SOD-1 was lower in the islets of the STZ-induced animals at all times studied and for GSH-Px in D10 and D30. Significance: Although STZ-induced diabetic rats presented compensatory mechanisms to restore the mass of endocrine cells, this was not sufficient since these rats developed the diabetic state. This was confirmed by the oral glucose tolerance test from D30. In addition, the delta (δ)-cells presented ectopic location in islets, indicating a possible relationship for beta (β)-cell mass restoration. There was a response of the pancreas to reduce the hyperglycemia in the first month of life. Furthermore, the cells from the endocrine pancreas of diabetic animals show a decline of antioxidant enzymatic, contributing to the increased susceptibility of cells to hyperglycemia-induced ROS in this postnatal critical development window.
Keywords: Glucagon; Insulin; Oxidative stress; Rats; Somatostatin